Fruit and Vegetable Peel-Enriched Functional Foods: Potential Avenues and Health Perspectives - Bhardwaj, Kanchan; Najda, Agnieszka; Sharma, Ruchi; Nurzyńska-Wierdak, Renata; Dhanjal, Daljeet Singh; Sharma, Rohit; Manickam, Sivakumar; Kabra, Atul; Kuča, Kamil; Bhardwaj, Prerna (Evidence-based complementary and alternative medicine, 2022)
Fresh fruit and vegetables are highly utilized commodities by health-conscious consumers and represent a prominent segment in the functional and nutritional food sector. However, food processing is causing significant loss of nutritional components, and the generation of waste is creating serious economic and environmental problems. Fruit and vegetables encompass husk, peels, pods, pomace, seeds, and stems, which are usually discarded, despite being known to contain potentially beneficial compounds, such as carotenoids, dietary fibers, enzymes, and polyphenols. The emerging interest in the food industry in the nutritional and biofunctional constituents of polyphenols has prompted the utilization of fruit and vegetable waste for developing enriched and functional foods, with applications in the pharmaceutical industry. Moreover, the utilization of waste for developing diverse and crucial bioactive commodities is a fundamental step in sustainable development. Furthermore, it provides evidence regarding the applicability of fruit and vegetable waste in different food formulations especially bakery, jam, and meat based products.